Facial pillars in dogs: an anatomical study - Kyllar, Michal; Paral, Vaclav; Pyszko, Martin; Doskarova, Barbora (Anatomical science international, 2017)
This study describes the facial pillar system in dolichocephalic and brachycephalic breeds of dogs, and highlights its differences. Knowledge of facial pillar system anatomy is imperative to carry out successful fracture repair. The aim of our study was to describe the pillar system of the facial skeleton in dogs, and compare different shapes of dog skulls using native skulls, radiographs and computed tomography (CT). The heads of brachycephalic and dolichocephalic dogs were investigated following a maceration process using trans-illumination, radiography and CT. Ground sections were created from bones of the facial skeleton for investigation of osteon directions. This study has revealed that the facial skeleton of the dog has numerous sinuses supported by vertically and horizontally oriented bone pillars. These pillars can be divided into five principal regions in dolichocephalic skulls and six principal regions in brachycephalic skulls. Radiographic imaging of both the brachiocephalic and dolichocephalic skulls was not capable of discerning bone pillars. Computed tomography transverse and horizontal section images discerned all pillars observed in the illuminated skulls.
Keywords: psi; Animals; Skull; lebka; Tomography, X-Ray Computed; počítačová rentgenová tomografie; Male; zvířata; mužské pohlaví; Dogs; ženské pohlaví; Female